-1=log(x+3)

Simple and best practice solution for -1=log(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=log(x+3) equation:


Simplifying
-1 = log(x + 3)

Reorder the terms:
-1 = glo(3 + x)
-1 = (3 * glo + x * glo)
-1 = (3glo + glox)

Solving
-1 = 3glo + glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-3glo' to each side of the equation.
-1 + -3glo = 3glo + -3glo + glox

Combine like terms: 3glo + -3glo = 0
-1 + -3glo = 0 + glox
-1 + -3glo = glox

Add '-1glox' to each side of the equation.
-1 + -3glo + -1glox = glox + -1glox

Combine like terms: glox + -1glox = 0
-1 + -3glo + -1glox = 0

Add '1' to each side of the equation.
-1 + -3glo + 1 + -1glox = 0 + 1

Reorder the terms:
-1 + 1 + -3glo + -1glox = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -3glo + -1glox = 0 + 1
-3glo + -1glox = 0 + 1

Combine like terms: 0 + 1 = 1
-3glo + -1glox = 1

Reorder the terms:
-1 + -3glo + -1glox = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + -3glo + -1glox = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(1 + 3glo + glox) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(1 + 3glo + glox)' equal to zero and attempt to solve: Simplifying 1 + 3glo + glox = 0 Solving 1 + 3glo + glox = 0 Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 3glo + -1 + glox = 0 + -1 Reorder the terms: 1 + -1 + 3glo + glox = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3glo + glox = 0 + -1 3glo + glox = 0 + -1 Combine like terms: 0 + -1 = -1 3glo + glox = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -25(0)+y=55 | | a-200=100 | | 3x=9+x+1 | | (3sinx)(3cosx)= | | -25x+0=55 | | 4x^2+26x=48 | | 4x^2+26=48 | | -(x-5)=2x-4 | | Ln(5x-4)=3 | | 10x+5x-3=8x+12 | | 9+s=-20 | | 30*x^2= | | 72.2=y-21.2 | | x^3-12x^2-27x-14=0 | | 6.5=y-2.2 | | x(x-3)=10.71 | | b-4=4 | | x+5=-21.5 | | sqrt(14x+8)=x+4 | | 150+10logx=40 | | 2/3(4y-4)/3 | | 6y=-25-7 | | -1*-0= | | -4(7a+5)=-160 | | 4x^2-24x+21=0 | | x+(x*0.07)=3103 | | x^2-3x=10.71 | | 7.6=d-5.2 | | 154=37x-14+19x | | 3/4x^2-48=0 | | -25=9 | | 15p=135 |

Equations solver categories